The Effectiveness of Using Documentary Film in Teaching Writing Report Text at the Eleventh Grade Students of SMA N 1 Prembun in the Academic Year of 2015/2016 - Sari Sri Lestari (Scripta : English Department Journal, 2019)
The objectives of this study were to know the students’ ability in writing report text and to find out whether the use of documentary film is effective or not in teaching writing report text at the eleventh grade students of SMA N 1 Prembun in the academic year of 2015/2016. This study was classified as a quasiexperimental research with a pre-test and post-test. The subject of this study was the eleventh grade students of SMA N 1 Prembun in the academic year of 2015/2016. The researcher took 56 students as the samples. They were 28 students of XI MIA 1 as the experimental group and 28 students of XI MIA 2 as the control group. The experimental group was taught using documentary film and the control group was taught using picture. In collecting the data, theresearcher used written test to get the data concerning the students’ writing ability. The result of the test was analyzed using t-test formula and SPSS. The result of the test showed that there was a significant difference between the experimental group and the control groups’ ability in writing report text after getting the treatment. The mean score of the experimental group post-test was 78.79 belonging to good level. Meanwhile, the mean score of the control group was 71.61 belonging to good level. Moreover, based on the calculation of t-test formula, it was found that the t-value was higher than the t-table by using 5% alpha of significance (6. 275 > 2.005). Based on the result above, it can be concluded that the use of documentary film is effective in teaching writing report text, particularly at the eleventh grade students of SMA N 1 Prembun in the academic year of 2015/2016.